An easy access to fused chromanones via rhodium catalyzed oxidative coupling of salicylaldehydes with heterobicyclic olefins. Issue 27 (7th July 2016) - Vijayan, Ajesh; Baiju, T.V.; Jijy, E.; Prakash, Praveen; Shimi, M.; Joseph, Nayana; Pihko, Petri M.; Varughese, Sunil; Radhakrishnan, K.V.
Abstract: Herein we describe a detailed study on the rhodium catalyzed oxidative coupling of salicylaldehydes with heterobicyclic olefins such as diazabicyclic olefins and urea-derived bicyclic olefins. The developed method provides an ideal route to fused chromanone systems in a single synthetic step. Moreover, the scope of this methodology was extended to different oxa/aza-bridged bicyclic urea derivatives. Graphical abstract: